(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
The term ‘utopia’ has been used by different tendencies and institutions, also the religious life, to show some ideas that mobilize their world projects. Latin-American theologian and humanist research hasn’t developed enough the relationship between utopia and religious life. Our research tries to determine the textual and contextual relation of the use (presence and absence) of utopia as a term, in the “Confederación Latinoamericana de Religiosas y Religiosos” (CLAR) journal between 1970 and 2000. We used the tools proposed by the Critical Discourse Analysis and lexicography. The results show some difficulty and heterogeneity to formulate and express utopia. Censure and profound differences in theological and eschatological issues are some of the reasons for that matter. In spite of that, Latin-American religious life tends to express the presence of utopia associated to Christian Kingdom utopia.